Female Leadership: Obstacles and Opportunities - Marta TAVEIRA; Susana SILVA (Communications of International Proceedings, 2021)
Women have the same levels and sometimes higher levels of training than men and account for about 50% of the workforce. Yet women are underrepresented in higher hierarchical positions. Cultural and social norms, as well as the responsibilities and roles of women, appear as some of the barriers that justify the lesser female presence in top positions. The purpose of this study is to characterize female leadership, by exploring its obstacles and opportunities. Interviews were made to ten women leaders. Data were analyzed according to Grounded Theory procedures and thematic analysis. The results of this study suggest that female leadership is characterized by some challenges, mainly gender bias and difficulties at personal, family and professional level, but it is mainly characterized by opportunities which appear through the support that the leaders receive, through the combination of some personal characteristics and also through the use of strategies that allow reconciliation of personal and professional life. Developmental practices, such as mentoring and coaching, are also conducive to female leadership. Finally, some opportunities were identified in the context of personal, family and professional life. It is possible to conclude that, although the executive world is still very masculine, the presence of women in top leadership positions is increasing. Even though this process is slow and gradual, women are positioning themselves to achieve even greater success in the future.
Keywords: Leadership development; gender stereotype; feminine leadership; work-life conflict.